Karyotype Evolution in Harvestmen of the Suborder Cyphophthalmi (Opiliones) - Svojanovská, Hana; Nguyen, Petr; Hiřman, Matyáš; Tuf, Ivan H; Wahab, Rodzay Abdul; Haddad, Charles R; Šťáhlavský, František (Cytogenetic and genome research, 2016)
The morphologically uniform suborder Cyphophthalmi represents a basal group of harvestmen (Opiliones). As such, it plays an important role in the reconstruction of the karyotype evolution within this arachnid order. The cytogenetic analysis of 6 representatives of the suborder Cyphophthalmi, namely Miopsalis sp. (2n = 30; Stylocellidae), Austropurcellia arcticosa (Cantrell, 1980) (2n = 30; Pettalidae), Parapurcellia amatola de Bivort & Giribet, 2010 (2n = 32; Pettalidae), Paramiopsalis aff. ramulosus Juberthie, 1962 (2n = 28; Sironidae), Cyphophthalmus duricorius Joseph, 1868 (2n = 24; Sironidae), and Siro carpaticus Rafalski, 1956 (2n = 52; Sironidae) was performed. Fluorescence in situ hybridization with 18S rDNA probe was used to analyze the distribution of major ribosomal RNA genes in harvestmen. We confront the obtained cytogenetic data with current hypotheses on cyphophthalmid phylogeny to reconstruct their karyotype evolution. We conclude that the ancestral karyotype of harvestmen consisted of 2n = 30 elements with 1 chromosome pair bearing terminal rDNA clusters. The rDNA locus was multiplicated in the evolution of Cyphophthalmi. However, decreases as well as increases in the number of chromosomes have been detected in the karyotype evolution of Cyphophthalmi. Our data thus reveal unexpected diversity in cyphophthalmid karyotypes.
Keywords: Arachnida; Evolution, Molecular; molekulární evoluce; karyotyp; Female; Animals; RNA, Ribosomal, 18S; ženské pohlaví; RNA ribozomální 18S; mužské pohlaví; Karyotype; pavoukovci; hybridizace in situ fluorescenční; Male; zvířata; fylogeneze; Phylogeny; In Situ Hybridization, Fluorescence